Improved functionality of roselle (Hibiscus sabdariffa) calyx extract blended Kombucha, a fermented beverage - G, Gayathry; T, Uma Maheswari; K, Jothilakshmi; S, Amutha (Plant Science Today, 2025)
Kombucha is a fermented drink with a range of medicinal benefits prepared from sweetened tea infusion (Camellia sinensis), which is cultured symbiotically with yeast and acetic acid bacteria. In the present investigation, kombucha was prepared from sugared black tea extract blended with aqueous calyx extract of roselle (Hibiscus sabdariffa) @15% and fermented with cultures viz., Komagataeibacter rhaeticus (NAIMCCTB-3976) and Brettanomyces bruxellensis (CAP9) at 35°C. The floating water insoluble mat of kombucha was observed under a scanning electron microscope, which revealed the cellulosic nanofibrils secreted by K. rhaeticus. The total phenolic and flavanoid content, DPPH, and ABTS activity of roselle calyx blended kombucha were significantly higher than black tea kombucha. Further, the compounds present in kombucha, when analyzed by fourier transform infra-red spectroscopy, denoted the presence of carbonyl compounds, aromatic olefinic compounds, ketones, aldehydes, and esters. The different bioactive metabolites formed during fermentation were elucidated using gas chromatography-mass spectrometry and the major compounds excited within the retention time of 45 min with maximum peak area were 13-hexyloxacyclotridec-10-en-2-one (37.64%), palmitins such as 1,3 dipalmitin (6.42%), glycidyl palmitate (3.30%), organic acids such as undecanedioic acid, linoleic acid, acetic acid (3.88%), etc. The results proved that blending black tea extract with 15% roselle calyx extract as a substrate for kombucha fermentation was highly accepted with an organoleptic score of 95% and improved functional properties compared to black tea extract kombucha alone.